Sedation among outpatient gastroscopy improve patients' overall satisfaction to gastroscopy service - Azmi, AN; Mahamad, UA; Solehan, HM; Rosaida, MS; Chan, WK; Ho, SH; Goh, KL (Wiley-Blackwell, 2024)
Indexed by WOS